Room temperature curing light epoxy adhesive and preparation method thereof

By adding modified hollow glass microbeads and modified silicon micropowder as composite fillers to the light epoxy adhesive cured at room temperature, and combining appropriate curing agents and accelerators, the problem of insufficient strength of room-temperature curing epoxy resin adhesives in the prior art is solved, and a high-strength bonding effect is achieved.

CN119709078APending Publication Date: 2025-03-28SHANGHAI HAIYING ADHESIVE TECH CO LTD

Patent Information

Application Number
CN202411638843.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing room-temperature cured epoxy resin adhesives have poor strength after curing, making it difficult to meet certain high-strength bonding needs.

Method used

Light epoxy adhesive with a mass ratio of (2~4): 1 and a lightweight epoxy adhesive with a mass ratio of (2~4): 1, modified hollow glass microbeads and modified silicon micropowder are added as composite fillers, and curing agent, silane coupling agent, calcium carbonate, accelerator and crosslinking agent are added to component B, and prepared by stirring and drying under vacuum conditions.

Benefits of technology

Lightweight epoxy adhesives that cure at room temperature have excellent strength and mechanical properties, and are suitable for applications requiring high-strength bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a room temperature curing light epoxy adhesive and a preparation method thereof, and belongs to the technical field of adhesives. Comprising a component A and a component B in a mass ratio of (2-4): 1, the component A comprises the following raw materials in parts by weight: 50-70 parts of epoxy resin, 15-25 parts of modified silicone rubber, 3-5 parts of a diluent, 15-30 parts of a composite filler and 2-5 parts of a plasticizer; the component B comprises the following raw materials: 40-50 parts of a curing agent, 1-3 parts of a silane coupling agent, 10-15 parts of calcium carbonate, 1-3 parts of an accelerant and 1-3 parts of a cross-linking agent; the prepared room temperature curing light epoxy adhesive has excellent strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives and relates to a room temperature curing lightweight epoxy adhesive and a preparation method thereof. Background Art

[0002] Regarding room temperature curing organic adhesives, the adhesive products currently developed include room temperature vulcanizing silicone rubber adhesives, room temperature curing epoxy structural adhesives and other heat-resistant adhesives, which are mainly used for bonding metals, rubbers, and other heat-resistant non-metallic materials.

[0003] Among them, epoxy resin has excellent physical, mechanical and electrical insulation properties, good adhesion to various materials, and flexible use process. Therefore, epoxy resin adhesives have been widely used in various fields.

[0004] However, the current room temperature curing epoxy resin adhesives have the characteristic of poor strength after curing, so it is necessary to develop a room temperature curing epoxy adhesive with higher strength. Summary of the invention

[0005] The object of the present invention is to provide a room temperature curing lightweight epoxy adhesive and a preparation method thereof. The prepared lightweight epoxy adhesive can be cured at room temperature and has excellent strength.

[0006] The purpose of the present invention can be achieved by the following technical solutions: A room temperature curing lightweight epoxy adhesive, comprising a component A and a component B in a mass ratio of (2-4):1; In parts by weight, the component A comprises the following raw materials: 50-70 parts of epoxy resin, 15-25 parts of modified silicone rubber, 3-5 parts of diluent, 15-30 parts of composite filler, and 2-5 parts of plasticizer; The B component comprises the following raw materials: 40-50 parts of curing agent, 1-3 parts of silane coupling agent, 10-15 parts of calcium carbonate, 1-3 parts of accelerator and 1-3 parts of cross-linking agent; The preparation process of the composite filler is as follows: In parts by weight, 10-15 parts of hydrogenated rosin are dissolved in 60-80 parts of anhydrous ethanol at 30-40° C., 2-5 parts of hollow glass microspheres are added, stirred for 1-3 hours, and dried at 90-100° C. for 4-7 hours to obtain modified hollow glass microspheres; The tea saponin was dissolved in deionized water to form a tea saponin solution with a mass fraction of 10-20%, and then silicon micropowder was added, stirred for 30 minutes, and then heated to 55-70°C, ultrasonically treated at a power of 200-300W for 10-15 minutes, and then dried at 95-100°C for 5-9 hours to obtain modified silicon micropowder, wherein the solid-liquid ratio of silicon micropowder to tea saponin solution was 1:18 g / mL; The composite filler is obtained by grinding the modified hollow glass microspheres and the modified silicon micropowder in a mass ratio of 1:1 by a ball mill at a rotation speed of 400 r / min for 5 hours.

[0007] As a preferred technical solution of the present invention, the diluent is one of ethylene glycol diglycidyl ether and 1,6-hexanediol diglycidyl ether.

[0008] As a preferred technical solution of the present invention, the plasticizer is one or more of dibutyl phthalate, dioctyl phthalate and dioctyl terephthalate.

[0009] As a preferred technical solution of the present invention, the curing agent is one or more of polyamide curing agent, ethylenediamine, diethylenetriamine and meta-xylylenediamine.

[0010] As a preferred technical solution of the present invention, the silane coupling agent is one of KH550, KH560 or KH570.

[0011] As a preferred technical solution of the present invention, the accelerator is one of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethylimidazole and 2-ethyl-4-methylimidazole.

[0012] As a preferred technical solution of the present invention, the cross-linking agent is one or more of glycidyl methacrylate, diethylene glycol diacrylate and trimethylolpropane triacrylate.

[0013] As a preferred technical solution of the present invention, the epoxy resin is bisphenol A epoxy resin.

[0014] As a preferred technical solution of the present invention, the preparation process of the modified silicone rubber is as follows: First, the glass fiber was ball-milled at a speed of 600-700 r / min for 2 h, and then the obtained solid was placed in a CVD furnace, nitrogen was introduced for protection, heated to 800°C and kept warm for 2 h, and then naturally cooled to room temperature to obtain pretreated glass fiber; In parts by weight, 30 to 35 parts of hydroxyl-terminated polydimethylsiloxane and 0.5 to 1.5 parts of ethyl orthosilicate are stirred at 30 to 40° C. for 20 to 25 minutes, and then 0.1 to 0.3 parts of butyltin dilaurate are added and stirred for 30 minutes and dried to obtain a mixture A, which is mixed with 80 to 100 parts of toluene and stirred for 15 to 25 minutes, and then 10 to 15 parts of pretreated glass fiber are added and stirred for 2 to 4 hours, and then allowed to stand and filtered. The obtained solid is washed with deionized water and dried at 80 to 100° C. for 5 to 8 hours to obtain the modified silicone rubber.

[0015] A method for preparing a room temperature curing lightweight epoxy adhesive comprises the following preparation steps: S1. According to the weight proportion of each raw material, the epoxy resin and the modified silicone rubber are first mixed evenly, and then kept in a constant temperature oven at 60-70°C for 2-4 hours, and then a diluent and a plasticizer are added and stirred at a speed of 300-400 r / min for 30 minutes to obtain a primary mixture; S2, drying the composite filler with hot air at 110-120°C for 2-4h and then cooling it naturally to room temperature, then adding the primary mixture and the composite filler into a reactor at 50-70°C, increasing the speed to 500-600r / min under vacuum -0.1Mpa conditions, continuing to stir for 20-30min to degas, and preparing component A; S3, adding a curing agent, a silane coupling agent, calcium carbonate, an accelerator and a cross-linking agent into a reaction kettle, stirring at a speed of 300-400 r / min for 30 min at room temperature, and then increasing the speed to 500-600 r / min under vacuum -0.1 MPa conditions, stirring for 20-30 min to degas, and preparing component B; S4. Mix component A and component B evenly according to the mass ratio to obtain the room temperature curing lightweight epoxy adhesive.

[0016] When preparing the composite filler, the hollow glass microspheres are first modified by hydrogenated rosin, and the hydrogenated rosin is dissolved in an organic solvent, and is used as a coating material to be uniformly coated on the surface of the hollow glass microspheres by physical methods, which can improve the surface properties of the hollow glass microspheres. The functional groups in the hydrogenated rosin are used to physically adsorb on the surface of the hollow glass microspheres, which can change the polarity and roughness of the surface of the hollow glass microspheres, and improve the compatibility and dispersibility with the polymer matrix material of the adhesive. In addition, hydrogenated rosin contains rigid groups such as phenanthrene rings. The hollow glass microspheres modified by hydrogenated rosin can more effectively interact with the polymer in the adhesive to form a stronger binding force, which helps to improve the strength of the adhesive.

[0017] Tea saponin, as a natural surfactant, can form a physical adsorption layer on the surface of silica powder through its intermolecular interaction, thereby changing the surface properties of silica powder. The introduction of tea saponin can increase the hydrophilicity and wettability of the surface of silica powder, making it easier to combine with the polymer matrix and improve compatibility. The modified silica powder can more effectively interact with the polymer chain in the adhesive and enhance the binding force.

[0018] Hollow glass microspheres are lightweight, high-strength glass spheres with a high strength / density ratio. Adding them to epoxy adhesives can produce a microsphere effect, reduce the amount of resin used, and give the adhesive better fluidity and processing performance. Silica powder has a series of advantages such as excellent dielectric properties, low thermal expansion coefficient, high thermal conductivity, and high chemical stability. Filling silica powder in epoxy adhesives as an inorganic functional filler can effectively reduce the linear expansion coefficient of the cured product and the shrinkage rate during curing, and improve the mechanical strength of the adhesive.

[0019] The modified hollow glass microspheres and silica powder are used as composite fillers. The lightweight, high-strength and good fluidity of the hollow glass microspheres help to form a uniform dispersion in the epoxy adhesive, reduce stress concentration, thereby improving the strength of the adhesive and helping the adhesive to cure better at room temperature. The excellent hardness, high thermal conductivity and chemical stability of silica powder are used to effectively reduce the curing shrinkage of the epoxy adhesive and reduce internal stress, thereby improving the mechanical strength of the adhesive. The two are used as composite fillers to jointly optimize the overall performance of the adhesive and improve the strength of the room temperature curing epoxy adhesive.

[0020] In the present invention, glass fiber is added to the silicone rubber. The glass fiber is firstly subjected to ball milling treatment to increase the surface active sites, making it easier to combine with the polymer, thereby further improving the compatibility of the glass fiber and the silicone rubber.

[0021] At the same time, due to the addition of glass fiber to the hydroxyl-terminated polydimethylsiloxane, the strength and hardness of the modified silicone rubber are improved through cross-linking agent treatment. After mixing with the epoxy resin, the introduction of the modified silicone rubber can form an interpenetrating network structure with the epoxy resin, thereby enhancing the overall strength and thermal stability of the epoxy resin.

[0022] Beneficial effects of the present invention: The epoxy adhesive prepared by the present invention comprises two components A and B. A composite filler obtained by mixing modified hollow glass microspheres and modified silicon micropowder by ball milling is added to the A component, and epoxy resin and modified silicone rubber are mixed to enhance the overall strength of the adhesive. After the A and B components are mixed, a lightweight epoxy adhesive with high strength that can be cured at room temperature can be prepared. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0024] In the following examples and comparative examples: Hollow glass microspheres: purchased from Shijiazhuang Wende Mineral Products Co., Ltd., item number: hollow glass microspheres; Hydroxyl-terminated polydimethylsiloxane: purchased from Wuhan Rongcan Biotechnology Co., Ltd.; Hydrogenated rosin: purchased from Hubei Jusheng Technology Co., Ltd.; Tea saponin: purchased from Wuhan Jiyesheng Chemical Co., Ltd., purity: 90%; Silica powder: purchased from Beijing Huawei Ruike Chemical Technology Co., Ltd. Glass fiber: purchased from Hubei Xinrunde Chemical Co., Ltd.; Tetraethyl orthosilicate: purchased from Wuhan Jiyesheng Chemical Co., Ltd.; Butyltin dilaurate: purchased from Jinan Century Tongda Chemical Co., Ltd., product number: 2466; Bisphenol A epoxy resin: purchased from Hubei Shixing Chemical Co., Ltd. Ethylene glycol diglycidyl ether: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: E823392; Dibutyl phthalate: purchased from Jinan Shanhai Chemical Technology Co., Ltd.; Polyamide curing agent: purchased from Shanghai Myril Biochemical Technology Co., Ltd., product number: M68944; KH550: purchased from Jinan Shanhai Chemical Technology Co., Ltd.; Calcium carbonate: Shanghai Juqian New Materials Development Co., Ltd., item number: 1; 2,4,6-Tris(dimethylaminomethyl)phenol: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: T769212; Glycidyl methacrylate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: G810426; KH560: purchased from Jinan Shanhai Chemical Technology Co., Ltd.; 2-Ethylimidazole: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: E822777.

[0025] Example 1 Preparation of composite fillers: In parts by weight, 10 parts of hydrogenated rosin were dissolved in 60 parts of anhydrous ethanol at 30° C., 2 parts of hollow glass microspheres were added, stirred for 1 hour, and dried at 90° C. for 4 hours to obtain modified hollow glass microspheres; Tea saponin was dissolved in deionized water to form a tea saponin solution with a mass fraction of 10%, and then silicon micropowder was added, stirred for 30 minutes, and then heated to 55°C, ultrasonically treated at a power of 200W for 10 minutes, and then dried at 95°C for 5 hours to obtain modified silicon micropowder, wherein the solid-liquid ratio of silicon micropowder to tea saponin solution was 1:18 g / mL; The composite filler is obtained by grinding the modified hollow glass microspheres and the modified silicon micropowder in a mass ratio of 1:1 by a ball mill at a rotation speed of 400 r / min for 5 hours.

[0026] Preparation of modified silicone rubber: First, the glass fiber was ball-milled at a speed of 600 r / min for 2 h, and then the obtained solid was placed in a CVD furnace, nitrogen was introduced for protection, heated to 800°C and kept warm for 2 h, and then naturally cooled to room temperature to obtain pretreated glass fiber; In parts by weight, at 30°C, 30 parts of hydroxyl-terminated polydimethylsiloxane and 0.5 parts of ethyl orthosilicate were stirred for 20 minutes, and then 0.1 parts of butyltin dilaurate were added and stirred for 30 minutes, and then dried to obtain a mixture A, which was mixed with 80 parts of toluene and stirred for 15 minutes. 10 parts of pretreated glass fibers were added and stirred for 2 hours, and then allowed to stand and filtered. The obtained solid was washed with deionized water and dried at 80°C for 5 hours to obtain the modified silicone rubber.

[0027] Preparation of room temperature curing lightweight epoxy adhesive: S1. According to the weight proportion of each raw material, 50 parts of bisphenol A epoxy resin and 15 parts of modified silicone rubber were mixed evenly, and then kept in a constant temperature oven at 60° C. for 2 hours, and then 3 parts of ethylene glycol diglycidyl ether and 2 parts of dibutyl phthalate were added and stirred at a speed of 300 r / min for 30 minutes to obtain a primary mixture; S2, 15 parts of the composite filler were first dried by hot air at 110°C for 2 hours and then naturally cooled to room temperature, and then the primary mixture and the composite filler were added to a 50°C reactor, and the speed was increased to 500r / min under vacuum -0.1Mpa conditions and continued to stir for 20 minutes to degas, and then component A was prepared; S3, adding 40 parts of polyamide curing agent, 1 part of KH550, 10 parts of calcium carbonate, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol and 1 part of glycidyl methacrylate into a reactor, stirring at a speed of 300 r / min for 30 min at room temperature, and then increasing the speed to 500 r / min and stirring for 20 min under vacuum -0.1 MPa conditions to degas, and then preparing component B; S4. Evenly mix component A and component B in a mass ratio of 2:1 to obtain a room temperature curing lightweight epoxy adhesive.

[0028] Example 2 Preparation of composite fillers: In parts by weight, 12 parts of hydrogenated rosin were dissolved in 70 parts of anhydrous ethanol at 35° C., 3 parts of hollow glass microspheres were added and stirred for 2 hours, and the modified hollow glass microspheres were obtained after drying at 95° C. for 6 hours; Tea saponin was dissolved in deionized water to form a tea saponin solution with a mass fraction of 15%, and then silicon micropowder was added, stirred for 30 minutes, and then heated to 60°C, ultrasonically treated at a power of 250W for 13 minutes, and then dried at 98°C for 7 hours to obtain modified silicon micropowder, wherein the solid-liquid ratio of silicon micropowder to tea saponin solution was 1:18 g / mL; The composite filler is obtained by grinding the modified hollow glass microspheres and the modified silicon micropowder in a mass ratio of 1:1 by a ball mill at a rotation speed of 400 r / min for 5 hours.

[0029] Preparation of modified silicone rubber: First, the glass fiber was ball-milled at a speed of 650 r / min for 2 h, and then the obtained solid was placed in a CVD furnace, nitrogen was introduced for protection, heated to 800°C and kept warm for 2 h, and then naturally cooled to room temperature to obtain pretreated glass fiber; In parts by weight, at 35° C., 33 parts of hydroxyl-terminated polydimethylsiloxane and 1 part of ethyl orthosilicate were stirred for 23 minutes, and then 0.2 parts of butyltin dilaurate were added and stirred for 30 minutes, and then dried to obtain a mixture A, which was mixed with 90 parts of toluene and stirred for 20 minutes. 13 parts of pretreated glass fiber were added and stirred for 3 hours, and then allowed to stand and filtered. The obtained solid was washed with deionized water and dried at 90° C. for 7 hours to obtain the modified silicone rubber.

[0030] Preparation of room temperature curing lightweight epoxy adhesive: S1. According to the weight proportion of each raw material, 60 parts of bisphenol A epoxy resin and 20 parts of modified silicone rubber were first mixed evenly, and then kept in a constant temperature oven at 65°C for 3 hours, and then 4 parts of ethylene glycol diglycidyl ether and 3 parts of dibutyl phthalate were added and stirred at a speed of 350 r / min for 30 minutes to obtain a primary mixture; S2, drying 20 parts of the composite filler by hot air drying at 115°C for 3 hours and then cooling naturally to room temperature, then adding the primary mixture and the composite filler into a 60°C reactor, increasing the speed to 550r / min under vacuum -0.1Mpa conditions, and continuing to stir for 25 minutes to degas, to prepare component A; S3, adding 45 parts of polyamide curing agent, 2 parts of KH550, 13 parts of calcium carbonate, 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol and 2 parts of glycidyl methacrylate into a reaction kettle, stirring at a speed of 350 r / min for 30 min at room temperature, and then increasing the speed to 550 r / min under vacuum -0.1 MPa conditions and stirring for 25 min to degas, and then preparing component B; S4. Evenly mix component A and component B in a mass ratio of 3:1 to obtain a room temperature curing lightweight epoxy adhesive.

[0031] Example 3 Preparation of composite fillers: In parts by weight, 13 parts of hydrogenated rosin were dissolved in 80 parts of anhydrous ethanol at 35° C., 5 parts of hollow glass microspheres were added and stirred for 3 hours, and then dried at 100° C. for 7 hours to obtain modified hollow glass microspheres; Tea saponin was dissolved in deionized water to form a tea saponin solution with a mass fraction of 20%, and then silicon micropowder was added, stirred for 30 minutes, and then heated to 70°C, ultrasonically treated at a power of 300 W for 15 minutes, and then dried at 100°C for 9 hours to obtain modified silicon micropowder, wherein the solid-liquid ratio of silicon micropowder to tea saponin solution was 1:18 g / mL; The composite filler is obtained by grinding the modified hollow glass microspheres and the modified silicon micropowder in a mass ratio of 1:1 by a ball mill at a rotation speed of 400 r / min for 5 hours.

[0032] Preparation of modified silicone rubber: First, the glass fiber was ball-milled at a speed of 700 r / min for 2 h, and then the obtained solid was placed in a CVD furnace, nitrogen was introduced for protection, heated to 800°C and kept warm for 2 h, and then naturally cooled to room temperature to obtain pretreated glass fiber; In parts by weight, at 40°C, 35 parts of hydroxyl-terminated polydimethylsiloxane and 1.5 parts of ethyl orthosilicate were stirred for 25 minutes, and then 0.3 parts of butyltin dilaurate were added and stirred for 30 minutes and dried to obtain a mixture A, which was mixed with 100 parts of toluene and stirred for 25 minutes, and then 15 parts of pretreated glass fiber were added and stirred for 4 hours, and then allowed to stand and filtered. The obtained solid was washed with deionized water and dried at 100°C for 8 hours to obtain the modified silicone rubber.

[0033] Preparation of room temperature curing lightweight epoxy adhesive: S1. According to the weight proportion of each raw material, 70 parts of bisphenol A epoxy resin and 25 parts of modified silicone rubber were first mixed evenly, and then kept in a constant temperature oven at 70°C for 4 hours, and then 5 parts of ethylene glycol diglycidyl ether and 5 parts of dibutyl phthalate were added and stirred at a speed of 400 r / min for 30 minutes to obtain a primary mixture; S2, drying 30 parts of the composite filler by hot air at 120°C for 4 hours and then cooling naturally to room temperature, then adding the primary mixture and the composite filler into a 70°C reactor, increasing the speed to 600r / min under vacuum -0.1Mpa conditions and continuing stirring for 30 minutes to degas, to prepare component A; S3, adding 50 parts of polyamide curing agent, 3 parts of KH560, 15 parts of calcium carbonate, 3 parts of 2-ethylimidazole and 3 parts of glycidyl methacrylate into a reaction kettle, stirring at a speed of 400 r / min for 30 min at room temperature, and then increasing the speed to 600 r / min under vacuum -0.1 MPa conditions and stirring for 30 min to degas, and then preparing component B; S4. Evenly mix component A and component B in a mass ratio of (2-4):1 to obtain a room temperature curing lightweight epoxy adhesive.

[0034] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the hollow glass microspheres in Comparative Example 1 are not modified by hydrogenated rosin, and the other operations are the same.

[0035] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that the silicon micropowder in Comparative Example 2 is not modified by tea saponin, and the other operations are the same.

[0036] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that the preparation process of the composite filler in Comparative Example 3 is as follows: hollow glass microspheres and silicon micropowder with a mass ratio of 1:1 are ground by a ball mill at a speed of 400 r / min for 5 hours to obtain the composite filler, that is, the hollow glass microspheres and silicon micropowder are not modified, and the other operations are the same.

[0037] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the silicone rubber used in Comparative Example 4 has not been modified, that is, no glass fiber is added during the preparation of the modified silicone rubber, and the other operations are the same.

[0038] Performance Test: 1. The adhesives prepared in Examples 1-3 and Comparative Examples 1-4 were squeezed onto the surface of titanium alloy TC4, with an adhesive coating thickness of 0.2 mm. After curing at room temperature for 14 days, a shear strength test was performed in accordance with GB / T7124-2008 standard. The test results are shown in Table 1; Table 1

[0039] 2. Perform 180° peel strength test according to GB / T2790-1995 standard, test hardness according to ASTM D-2240, and test viscosity at 25°C according to ASTM D-2393. The test results are shown in Table 2:

[0040] According to the above data, the shear strength, peel strength and hardness of Examples 1-3 are higher than those of Comparative Examples 1-4. Therefore, the adhesive prepared by the present invention has stronger mechanical properties.

[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A room temperature curing lightweight epoxy adhesive, characterized in that: It includes component A and component B in a mass ratio of (2-4):1; In parts by weight, the component A comprises the following raw materials: 50-70 parts of epoxy resin, 15-25 parts of modified silicone rubber, 3-5 parts of diluent, 15-30 parts of composite filler, and 2-5 parts of plasticizer; The B component comprises the following raw materials: 40-50 parts of curing agent, 1-3 parts of silane coupling agent, 10-15 parts of calcium carbonate, 1-3 parts of accelerator and 1-3 parts of cross-linking agent; The preparation process of the composite filler is as follows: In parts by weight, 10-15 parts of hydrogenated rosin are dissolved in 60-80 parts of anhydrous ethanol at 30-40° C., 2-5 parts of hollow glass microspheres are added, stirred for 1-3 hours, and dried at 90-100° C. for 4-7 hours to obtain modified hollow glass microspheres; The tea saponin was dissolved in deionized water to form a tea saponin solution with a mass fraction of 10-20%, and then silicon micropowder was added, stirred for 30 minutes, and then heated to 55-70°C, ultrasonically treated at a power of 200-300W for 10-15 minutes, and then dried at 95-100°C for 5-9 hours to obtain modified silicon micropowder, wherein the solid-liquid ratio of silicon micropowder to tea saponin solution was 1:18 g / mL; The composite filler is obtained by grinding the modified hollow glass microspheres and the modified silicon micropowder in a mass ratio of 1:1 by a ball mill at a rotation speed of 400 r / min for 5 hours.

2. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The diluent is one of ethylene glycol diglycidyl ether and 1,6-hexanediol diglycidyl ether.

3. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The plasticizer is one or more of dibutyl phthalate, dioctyl phthalate and dioctyl terephthalate.

4. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The curing agent is one or more of polyamide curing agent, ethylenediamine, diethylenetriamine and meta-xylylenediamine.

5. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The silane coupling agent is one of KH550, KH560 or KH570.

6. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The accelerator is one of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethylimidazole and 2-ethyl-4-methylimidazole.

7. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The crosslinking agent is one or more of glycidyl methacrylate, diethylene glycol diacrylate and trimethylolpropane triacrylate.

8. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.

9. The room temperature curing lightweight epoxy adhesive according to claim 1, characterized in that: The preparation process of the modified silicone rubber is as follows: First, the glass fiber was ball-milled at a speed of 600-700 r / min for 2 h, and then the obtained solid was placed in a CVD furnace, nitrogen was introduced for protection, heated to 800°C and kept warm for 2 h, and then naturally cooled to room temperature to obtain pretreated glass fiber; In parts by weight, 30 to 35 parts of hydroxyl-terminated polydimethylsiloxane and 0.5 to 1.5 parts of ethyl orthosilicate are stirred at 30 to 40° C. for 20 to 25 minutes, and then 0.1 to 0.3 parts of butyltin dilaurate are added and stirred for 30 minutes and dried to obtain a mixture A, which is mixed with 80 to 100 parts of toluene and stirred for 15 to 25 minutes, and then 10 to 15 parts of pretreated glass fiber are added and stirred for 2 to 4 hours, and then allowed to stand and filtered. The obtained solid is washed with deionized water and dried at 80 to 100° C. for 5 to 8 hours to obtain the modified silicone rubber.

10. A method for preparing a room temperature curing lightweight epoxy adhesive as claimed in any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1. According to the weight proportion of each raw material, the epoxy resin and the modified silicone rubber are first mixed evenly, and then kept in a constant temperature oven at 60-70°C for 2-4 hours, and then a diluent and a plasticizer are added and stirred at a speed of 300-400 r / min for 30 minutes to obtain a primary mixture; S2, drying the composite filler with hot air at 110-120°C for 2-4h and then cooling it naturally to room temperature, then adding the primary mixture and the composite filler into a reactor at 50-70°C, increasing the speed to 500-600r / min under vacuum -0.1Mpa conditions, continuing to stir for 20-30min to degas, and preparing component A; S3, adding a curing agent, a silane coupling agent, calcium carbonate, an accelerator and a cross-linking agent into a reaction kettle, stirring at a speed of 300-400 r / min for 30 min at room temperature, and then increasing the speed to 500-600 r / min under vacuum -0.1 MPa conditions, stirring for 20-30 min to degas, and preparing component B; S4. Mix component A and component B evenly according to the mass ratio to obtain the room temperature easily curable lightweight epoxy adhesive.

Citation Information

Patent Citations

  • Room temperature curing high-temperature-resistant high-tenacity epoxy adhesive and preparation method thereof

    CN104804691A

  • Strain coordination layer for integral forming of ablative thermal protection structure as well as preparation method thereof and application

    CN111136935A

  • Room temperature curing two-component epoxy adhesive and production process thereof

    CN116144305A

  • Epoxy resin composition, adhesive film and light sealing material

    CN118496792A

Cited By

  • High-performance epoxy resin and cloud sand aluminized zinc tile

    CN120535914A